Parasympathetic functioning and sleep problems in children with autism spectrum disorder. Issue 11 (16th September 2022) - Schiltz, Hillary K.; Fenning, Rachel M.; Erath, Stephen A.; Baker, Jason K.
Abstract: Respiratory sinus arrhythmia (RSA), an index of parasympathetic nervous system activity, has been linked with sleep quality among children with neurotypical development. The current study extended examination of these processes to children with autism spectrum disorder (ASD), a group at considerable risk for sleep problems. Participants included 54 children with ASD (aged 6–10 years, 43% Hispanic). RSA data were collected via a wired MindWare system during a 3‐min baseline and a 3‐min challenge task. Parents reported on their children's sleep problems and sleep duration using the Children's Sleep Habits Questionnaire, Abbreviated. Although no significant correlations emerged between RSA indices and parent‐reported child sleep, baseline RSA and RSA reactivity interacted in the prediction of sleep problems. For children with higher RSA reactivity, higher baseline RSA was associated with fewer sleep problems, but for children with lower RSA reactivity, baseline RSA was not predictive. No main effects or interactions of RSA predicted sleep duration. Findings suggest resilience against sleep problems for children with ASD presenting with higher baseline RSA and higher RSA reactivity. Implications of these results center upon directly targeting psychophysiology (i.e., parasympathetic nervous system regulation) as a possible mechanism to improve sleep in children with ASD, and developing personalized interventions based on physiological markers of risk and resilience. Lay Summary: Children with autism spectrum disorder (ASD) often have difficulty sleeping, but contributing factors are not well understood. Findings suggest that certain psychophysiological tendencies thought to represent better overall arousal regulation and greater physiological reactivity to challenge may protect against sleep difficulties in children with ASD. Implications highlight the potential for targeting psychophysiological regulation as an avenue for reducing sleep problems.